Pengaruh Layanan Bimbingan Kelompok Dalam Meningkatkan Kemampuan Interaksi Sosial Siswa - Syafira Ghaisani Zaman; Widiastuti, Haning Tri (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
ABSTRACT "The Influence of Group Tutoring Services in Improving the Social Interaction Skills of Students". Thesis, Jakarta: Guidance and Counseling Study Program and Faculty of Teacher Training and Education, Muhammadiyah University Prof. DR HAMKA, 2024. Social interaction is an activity carried out by individuals or groups to connect with each other. However, at SMPN 1 Cibinong there are several class VII students who low social interaction skills, so efforts are needed to improve social interaction skills by using group tutoring services. The aim of this research is to improve social interaction skills through group guidance services for class VII at SMPN 1 Cibinong. This research uses the Experimental One Group Pre-test and Post-test research method. The population used was 440 class VII students at SMPN 1 Cibinong, with a research sample of 10 students, using a purposive sampling technique. Test the hypothesis using the -T test. Based on the results of calculations using SPSS, it is obtained that t count > t table, with a value of 12,764 > 1,833, then Ho is rejected and Ha is accepted, which means that influential group guidance services are carried out to improve students' social interaction abilities KEYWORDS:  Influence, Group guidance, social interaction abilities